(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To compare treatment outcomes of pediatric flat warts using topical 10% zinc sulphate solution and 10% salicylic ointment, and to analyze clinical factors influencing treatment response for the two regimens. Methods: This study was conducted from September 2024 to July 2025 at the National Hospital of Dermatology and Venereology. Sixty-two patients with flat warts were randomly assigned to receive either topical 10% zinc sulphate solution or 10% salicylic ointment for four weeks. Treatment outcomes were evaluated based on the reduction in the number of lesions. Clinical factors analyzed included age, lesion distribution, lesion count, disease duration, and lesion location. Results: Topical 10% zinc sulphate demonstrated a higher good-response rate than 10% salicylic ointment across several clinical subgroups. In patients with scattered lesions, the good-response rate in the zinc sulphate group reached 64.9%, compared with only 10.0% in the salicylic group (p<0.05). Among patients with disease duration of less than three months, the good-response rate was 57.1% in the zinc sulphate group, whereas no complete response was observed in the salicylic group (p<0.05). In patients with fewer than 30 baseline lesions, zinc sulphate achieved a significantly higher good-response rate than salicylic (50% vs. 12%; p<0.05). For facial lesions, the zinc sulphate group achieved a good-response rate of 48.2%, more than twice that of the salicylic group (21.7%; p=0.05). Conclusion: Topical 10% zinc sulphate is more effective than 10% salicylic ointment in the treatment of pediatric flat warts, particularly in specific patient subgroups. Clinical factors such as lesion count, lesion distribution, disease duration, and lesion location may help guide the selection of an appropriate treatment regimen.